Associations between cortical microinfarcts and MRI markers of neurodegeneration and cerebrovascular disease in aging. (1st February 2022) - Sadaghiani, Shokufeh; Dolui, Sudipto; Tisdall, Dylan M.; Tackett, William; Wolk, David A.; Detre, John A.
Abstract: Background: Cortical microinfarcts (CMI) are associated with cognitive impairment in both healthy aging and dementia, though the mechanisms underlying CMIs remain uncertain. Here we assessed correlations between CMIs and medial temporal lobe (MTL) cortical thickness, white matter hyperintensity (WMH) volume, and cerebral blood flow (CBF) in older subjects. Method: Neuroimaging data from 55 cognitively intact older subjects scanned using a hybrid 7T/3T protocol were analyzed. CMIs were manually identified on T1‐weighted MP2RAGE data (0.7mm isotropic resolution) obtained at 7T (Figure 1). Cortical thickness, WMH volume and whole brain CBF were obtained with T1‐weighted, FLAIR and 3D background suppressed arterial spin labeling (ASL) imaging, all acquired at 3T and were available from N=39, 49 and 48 subjects of the N=55 subjects respectively. Spearman's bivariate nonparametric test was used for statistical analyses. Result: Cohort demographics and imaging results are summarized in Table 1. 111 CMIs were detected in 43 of 55 (78%) of 7T T1‐weighted and FLAIR MRI scans (range:0‐6, 56% multiple CMIs). Age and sex were not significantly correlated with the number of CMIs. A negative correlation between the number of CMIs and mean BA36 cortical thickness was observed (r(37)= ‐0.348, p=0.03) (Figure 2). A similar trend was also observed in entorhinal and parahippocampal cortices. No significant correlation was seen between the number of CMIs and WMH volume. No significant correlation was observed between the number of CMIs and CBF in whole brain, gray matter, or white matter. Conclusion: The percentage of subjects showing CMIs is higher than previous 3T studies suggesting improved sensitivity of high‐resolution 7T MRI for detection of CMIs. Contrary to prior reports the lack of correlation between the number of CMIs and either WMH volume or CBF suggests that cerebrovascular insufficiency and small vessel ischemic disease may not be the underlying pathologic mechanisms causing CMIs, at least in cognitively intact older subjects. However, the negative correlation between CMIs and MTL cortical thickness supports the possibility of a mutual underlying pathway for Alzheimer's disease and CMIs that may be mediated by cerebral amyloid angiopathy.